An approach to balance state of charges of distributed batteries in virtual power plants of dc distribution network - Duc, Nguyen Huu (Vietnam Journal of Science and Technology, 2018)
Small distributed energy sources could be aggregated to form a virtual power plant (VPP) in order to overall improve technical and market issues. VPPs should be composed of several distributed batteries (DB) to solve the problem of intermittency due to wind and solar. This paper presents an approach to balance state of charge batteries. It is therefore to improve the lifetime of batteries in VPPs. According to the proposed method, the real-time SOC of DB will be tracking on the balancing SOC determined in VPP. During operation, the difference of SOC among DBs will be shrunk and finally the share of exchange power among DB is equal. Moreover, the duration time to achieve the balancing SOC can be determined by adjusting the exponent parameter of SOC in the presented function.